The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.9778/cmajo.20190047
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of diabetic ketoacidosis at diabetes diagnosis among children in Quebec: a population-based retrospective cohort study

Abstract: Background: Diabetic ketoacidosis at type 1 diabetes diagnosis is a preventable life-threatening complication. Canadian data on the temporal trends of the prevalence of diabetic ketoacidosis at the onset of type 1 diabetes in children are unknown. We aimed to determine the temporal changes in diabetic ketoacidosis prevalence at diabetes diagnosis in Quebec. Methods: We conducted a population-based cohort study of children (aged 1-17 yr) living in Quebec who were diagnosed with diabetes between 2001 and 2014, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Diabetic ketoacidosis (DKA) is seen in up to 50% of youth at presentation [17,18]. Forty-five per cent of children present with type 1 diabetes before 10 years of age [19] but there are two peaks in the age of presentation, the first at 4-6 years and the second at 10-14 years.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Diabetic ketoacidosis (DKA) is seen in up to 50% of youth at presentation [17,18]. Forty-five per cent of children present with type 1 diabetes before 10 years of age [19] but there are two peaks in the age of presentation, the first at 4-6 years and the second at 10-14 years.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…5,6 Canadian data suggest recent prevalence rates of 18.6% to 25.6%. 7,8 Healthcare provider perceptions suggest a delay in diagnosis of children with new onset DM1 during the COVID-19 pandemic due to possible fears around virus transmission during healthcare appointments and under-recognition of symptoms secondary to reduced face-to-face interactions with medical providers. 9 Recent evidence has emerged showing an increase in severe ketoacidosis at diabetes diagnosis in children in Germany, Italy, and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…10 A study from the province of Quebec found that the rate of DKA at diagnosis of diabetes increased from 22% in 2001 to 30% in 2014, but the rates of DKA after diagnosis were not examined. 16 The factors contributing to the development of DKA at vs after diagnosis of type 1 diabetes are likely to be distinctive, and therefore it is of value to understand them as separate events to design effective preventative interventions. The objective of this study was to describe 11-year trends in the incidence of DKA at and after the diagnosis in a population-based cohort of individuals diagnosed with type 1 diabetes || Accepted Version || J Pediatr.…”
Section: Introductionmentioning
confidence: 99%